Magnetically Driven Self-Degrading Zinc-Containing Cystine Microrobots for Treatment of Prostate Cancer - Ussia, Martina; Urso, Mario; Kratochvilova, Monika; Navrátil, Jiří; Balvan, Jan; Mayorga-Martinez, Carmen C; Vyskocil, Jan; Masarik, Michal; Pumera, Martin (Small, 2023)
Prostate cancer is the most commonly diagnosed tumor disease in men, and its treatment is still a big challenge in standard oncology therapy. Magnetically actuated microrobots represent the most promising technology in modern nanomedicine, offering the advantage of wireless guidance, effective cell penetration, and non-invasive actuation. Here, new biodegradable magnetically actuated zinc/cystine-based microrobots for in situ treatment of prostate cancer cells are reported. The microrobots are fabricated via metal-ion-mediated self-assembly of the amino acid cystine encapsulating superparamagnetic Fe3 O4 nanoparticles (NPs) during the synthesis, which allows their precise manipulation by a rotating magnetic field. Inside the cells, the typical enzymatic reducing environment favors the disassembly of the aminoacidic chemical structure due to the cleavage of cystine disulfide bonds and disruption of non-covalent interactions with the metal ions, as demonstrated by in vitro experiments with reduced nicotinamide adenine dinucleotide (NADH). In this way, the cystine microrobots served for site-specific delivery of Zn2+ ions responsible for tumor cell killing via a "Trojan horse effect". This work presents a new concept of cell internalization exploiting robotic systems' self-degradation, proposing a step forward in non-invasive cancer therapy.
Keywords: Prostatic Neoplasms; zinek; Cystine; lidé; cystin; mužské pohlaví; Zinc; Male; nádory prostaty; Humans